2019
DOI: 10.1101/553867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corneal Biomechanical Alterations in Patients with Chronic Ocular Graft Versus-host Disease

Abstract: 22Purpose: To compare corneal biomechanics between patients with ocular graft versus-host 23 disease (oGVHD) and healthy subjects (controls), and to further correlate these values with 24 ocular and hematological characteristics. 25 Materials and Methods: The following procedures were performed in oGVHD patients and 26 controls: Schirmer test (ST), break-up time (BUT), corneal and conjunctival staining, tear 27 matrix metalloproteinase-9 (MMP-9) assay (InflammaDry test, Rapid Pathogen Screening, 28 Inc, Saraso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…If InflammaDry can reflect tear concentrations of MMP-9 quantitatively, this may play a crucial role in determining the severity of inflammation and improve the outcomes for dry eye patients beyond a simple diagnosis. Furthermore, clinical interpretation of the faint test (red) line during examination can be ambiguous, particularly because conditions involving deficiency of aqueous tears (such as Sjögren syndrome 19 or ocular graft-versus-host disease 20 ) yield negative results despite severe signs and symptoms of dry eye. Therefore, we need to know exactly how the results of the kit change as tear volume changes.…”
Section: Introductionmentioning
confidence: 99%
“…If InflammaDry can reflect tear concentrations of MMP-9 quantitatively, this may play a crucial role in determining the severity of inflammation and improve the outcomes for dry eye patients beyond a simple diagnosis. Furthermore, clinical interpretation of the faint test (red) line during examination can be ambiguous, particularly because conditions involving deficiency of aqueous tears (such as Sjögren syndrome 19 or ocular graft-versus-host disease 20 ) yield negative results despite severe signs and symptoms of dry eye. Therefore, we need to know exactly how the results of the kit change as tear volume changes.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring corneal hysteresis may improve the severity grading accuracy of oGVHD, as corneal biomechanical changes are closely associated with ocular surface inflammation. 81 Arafat, et al found elevated levels of neutrophil elastase, MMP-8 (matrix metalloproteinase) and MMP-9 and myeloperoxidase in tears of patients with oGVHD. 82 Also, certain proteins neutrophil extracellular traps (NET) and NET associated proteins are seen with the ocular surface desiccation, fibrotic eyelid changes and persistent inflammation in oGVHD.…”
Section: Overview Of Chronic Ogvhdmentioning
confidence: 99%
“…Also, a recent prospective study by Giannaccare et al showed measurably different corneal biomechanical changes in corneal hysteresis and resistance factor as compared to controls. 81 They proposed that corneal stromal collagen fibril architecture changes due to oGVHD may lead to these biomechanical changes. Corneal hysteresis and resistance factor may be used as a possible indicator of disease severity and progression in the future.…”
Section: Diagnosis Of Chronic Ogvhdmentioning
confidence: 99%
“…Previous immunohistochemical analyses of conjunctival samples disclosed the expression of MMP-9 in severely affected ocular GVHD forms [14]. Moreover, MMP-9 was found to be increased in tears and ocular surface tissues of chronic GVHD patients, compared with healthy subjects [15,16].…”
Section: Introductionmentioning
confidence: 99%